Solitary Renal Metastases From Stage IA Primary Lung Adenocarcinoma With Co‐Alteration of EGFR, RB1, and MAP3K1: A Case Report - Zhu Qin; Chen Xin; He Zhenzhen; Xie Liang; Yi Wei; Li Shuben (The Clinical Respiratory Journal)
ABSTRACT We report a case of 59‐year‐old female with solitary bilateral renal metastases after surgery of stage IA primary lung adenocarcinoma who underwent next‐generation sequencing (NGS) of both lesions. The patient received right upper lobectomy and lymph node dissection, which revealed primary invasive lung adenocarcinoma (pT1cN0M0, stage IA3). Two years following this, positron emission tomography–computed tomography (PET/CT) revealed multiple masses in both kidneys without other distant metastases, and ultrasonography‐guided puncture biopsy indicated the presence of metastatic lung adenocarcinoma. The NGS of both the primary and metastatic lesions revealed the co‐alteration of epidermal growth factor receptor (EGFR), RB transcriptional corepressor 1 (RB1), and mitogen‐activated protein kinase kinase 1 (MAP3K1), which is potentially associated with the risk of renal metastasis in early postoperative non‐small cell lung cancer.